Tax Robbery Incorporated: The transnational legal infrastructures of tax arbitrage - Philip Liste (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2022)
In the media, the so-called cum/ex trades were addressed as the biggest tax robbery in history. In a few years, the financial trading scheme caused an estimated damage to European state treasuries of ca. 50 billion euros. Through highly complex transactions, a network of equity traders, banks, super-rich investors, and lawyers generated returns of capital income tax that had never been paid before. In 2019, two involved British traders were put on trial in Bonn, Germany. Due to their cooperative behaviour, they received only mild sentences. Yet, this first cum/ex lawsuit has been a critical starting point for a wave of trials to follow. Observing the trial, the paper focuses on the role of law in the cum/ex industry. First, law is addressed not as constraining but enabling tax-driven equity - as an infrastructure that makes dark finance possible. Second, this legal infrastructure is not fixed but depends on an ongoing legal practice. And third, the infrastructure used for dark finance is not limited to domestic law. Rather, the relevant trading structures involve a series of transnational transactions, which are subject to various regulatory regimes, domestic and international, as well as public and private.
urn:nbn:de:hbz:465-20220427-112952-5
Keywords: 320; Cum/ex; global tax governance; legal infrastructure; transnational law; white-collar crime; finance; court ethnography; practice; expertise; law and society studies